Bilateral sleeve fractures of the patella in a 12-year-old boy with hereditary spastic paraparesis and crouch gait. (4th December 2013) - Malone, Ailish; Kiernan, Damien; O Brien, Tim
Abstract : This is the first reported case of bilateral sleeve fractures of the patellae in a child with crouch gait. A 12-year-old boy with hereditary spastic paraparesis (HSP), who was found to have mid-stance crouch of 20° on previous gait analysis, presented with pain of gradual onset and limited mobility. There was no history of trauma. Three-dimensional gait analysis showed that extensor mechanism function during loading response was intact, but knee flexion in swing was significantly reduced, indicating protective guarding by rectus femoris. X-rays showed bilateral minimally displaced sleeve fractures of the patellae. These were treated with immobilisation in cylinder casts in extension for 4 weeks. Follow-up X-rays showed that the fractures had successfully united and the patient progressed to full weight bearing and mobility as tolerated.